2013
DOI: 10.1051/e3sconf/20130126006
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic metabolites in humans after ingestion of wakame seaweed

Abstract: Abstract. Seaweed contains large amounts of various arsenic compounds such as arsenosugars (AsSugs), but their relative toxicities have not yet been fully evaluated. A risk evaluation of dietary arsenic would be necessary. After developing an arsenic speciation analysis of wakame seaweed (Undaria pinnatifida), we conducted a wakame ingestion experiment using volunteers. Five volunteers ingested 300 g of commercial wakame after refraining from seafood for 5 days. Arsenic metabolites in the urine were monitored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Ma and Le observed about 4.5 times increase of urinary DMA concentration from <20 μg/L in urine collected before ingestion to 90 μg/L in urine collected 26.5 h after the ingestion of 10 g yakinori seaweed. 64 Hata et al 86 observed significant increases in the excretion rate of DMA at 24 h after ingestion of wakame seaweed: 2.14 μg As/h vs 0.38 μg As/h. A total of 176.3 μg/L of arsenic (DMA proportion was over 50%) was excreted over 5 days after the ingestion of 300 g of wakame seaweed.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Ma and Le observed about 4.5 times increase of urinary DMA concentration from <20 μg/L in urine collected before ingestion to 90 μg/L in urine collected 26.5 h after the ingestion of 10 g yakinori seaweed. 64 Hata et al 86 observed significant increases in the excretion rate of DMA at 24 h after ingestion of wakame seaweed: 2.14 μg As/h vs 0.38 μg As/h. A total of 176.3 μg/L of arsenic (DMA proportion was over 50%) was excreted over 5 days after the ingestion of 300 g of wakame seaweed.…”
Section: Introductionmentioning
confidence: 98%
“…Hata et al observed significant increases in the excretion rate of DMA at 24 h after ingestion of wakame seaweed: 2.14 μg As/h vs 0.38 μg As/h. A total of 176.3 μg/L of arsenic (DMA proportion was over 50%) was excreted over 5 days after the ingestion of 300 g of wakame seaweed . A study on 16 volunteers in Korea with total arsenic 6.98 mg/person/day through seafood consumption found significant increases of total urinary arsenic with primary increase of DMA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wakame (soaked in 10 min) and kombu (soaked in 1 min) have an arsenic content of 34.7 and 51.2 µg/g, respectively 9 . The detection of arsenic metabolites in humans after ingesting wakame has been reported 10 .…”
Section: Introductionmentioning
confidence: 99%